Healthcare resource utilization and cost of pneumococcal disease in children in Germany, 2014–2019: a retrospective cohort study - Tianyan Hu; Bélène Podmore; Rosemarie Barnett; Dominik Beier; Wolfgang Galetzka; Nawab Qizilbash; Dennis Heckl; Timo Boellinger; Jessica Weaver (Pneumonia, 2023)
Abstract Background Since the introduction of higher valency pneumococcal conjugate vaccines in 2009, recent estimates on the economic burden of pediatric pneumococcal disease (PD) in Germany have been lacking. This study estimates healthcare resource utilization (HCRU) and medical cost associated with PDs in children < 16 years old in Germany from 2014–2019. Methods A nationally representative sample from the Institute for Applied Health Research (InGef) German claims database was used, covering approximately 5% of the total German population. Episodes of pneumococcal pneumonia (PP), all-cause pneumonia (ACP), invasive pneumococcal disease (IPD), and acute otitis media (AOM) in children aged < 16 years were identified using ICD-10-GM codes. HCRU was estimated from annual rates of outpatient visits, outpatient antibiotic prescriptions and inpatient admissions, divided by person-years (PY) at-risk. Average direct medical costs per episode were estimated as the total cost of all HCRU, divided by the total number of episodes. The Mann–Kendall test was used to assess monotonic time trends from 2014–2019. Results  During 2014–2019, 916,805 children aged < 16 years were followed up for a total of 3,608,716 PY. The average costs per episode for out-versus inpatient care associated with PP and ACP were €67 (95% CI 58–76) versus €2,606 (95% CI 1,338–3,873), and €63 (95% CI 62–63) versus €620 (95% CI 598–641), respectively. For IPD, the average medical cost per episode for out-versus inpatients were €30 (95% CI 19–42) versus €6,051 (95% CI 3,323–8,779), respectively. There were no significant trends in HCRU or costs for IPD or pneumonia over the study period, except for a significant reduction in ACP outpatient visits. A significant decrease in rate of outpatient visits and antibiotic prescribing for recurrent AOM was observed, in addition to an increase in rates of hospital admissions for simple AOM. This was paralleled by a significant increase in inpatient costs per episode for treating AOM overall, and simple AOM, over the study period. Conclusions  The HCRU and cost per episode of pneumonia and IPD did not vary significantly from 2014–2019, but increased for AOM. The economic burden of pneumonia, IPD, and AOM remains substantial in Germany.